Gratitude and Life Satisfaction among Older Adults in Saudi Arabia: Social Support and Enjoyment of Life as Mediators - Mogeda El Sayed El Keshky; Shatha Jamil Khusaifan; Feng Kong (Behavioral Sciences)
This cross-sectional study aimed to investigate the relationship between gratitude and life satisfaction, and the mediation role of social support and enjoyment of life among older individuals. The measures employed include the Gratitude, Resentment, and Appreciation test; the Enjoyment of Life scale; the Satisfaction with Life scale; and the Multidimensional Scale of Perceived Social Support. These were administered to a sample of 260 older individuals aged between 60 and 80. The main findings revealed a positive association between gratitude and life satisfaction, and social support was a partial mediator in this relationship. Although enjoyment of life was not a direct mediator in the relationship between gratitude and life satisfaction, the final model indicated a significant serial pathway from gratitude to social support and then through enjoyment of life to life satisfaction. In conclusion, enhancing gratitude, promoting the enjoyment of life, and social support to older individuals might increase their life satisfaction, which in turn might contribute to their successful aging.